Impact of physical exercise on sleep quality in college students: A Chain mediating role of self-efficacy and emotional control - Wen-Hao Zhang; Wei-dong Zhu; Hu Lou; Ding-you Zhang; Fan-zheng Mu; Xin-Yu Zhang; Yu-Han Li; Hao-jie Zuo; Qi Liu; Mo-han He; Jia-qiang Wang; Chen-Xi Li; et al. (PLoS ONE, 2026)
Objective The study aims to examine the impact of physical exercise on sleep quality among college students and elucidate the mediating roles of self-efficacy and emotional control in this relationship. Methods Data were obtained from the 2024 China College Students’ Physical Activity and Health Tracking Survey (CPAHLS-CS). A sample of 10,970 college students was included. Physical exercise levels were measured using the Physical Activity Rating Scale-3 (PARS-3), sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), self-efficacy was measured using the General Self-Efficacy Scale (GSES), and emotional control was assessed using the Adolescent Psychological Resilience Scale. Regression analysis and Bootstrap mediation analysis were employed to test the hypothesised relationships. Results (1) The direct effect of physical exercise on sleep quality was not significant (β = 0.011, P > 0.05). However, the total effect was negative (β = −0.056, P < 0.001), indicating that indirect effects comprised the predominant mechanism. (2) Self-efficacy (effect size = −0.024) and emotional control (effect size = −0.022) each independently mediated the relationship between physical exercise and sleep quality. (3) In the pathway through which physical exercise influences sleep quality, self-efficacy, and emotional control functioned as independent mediating variables. Specifically, physical exercise indirectly improved sleep quality by enhancing self-efficacy while positively impacting sleep quality through a distinct mediating mechanism involving strengthening emotional control. Conclusions This study demonstrates the influence of physical exercise, self-efficacy, and emotional control on sleep quality. The findings suggest that physical exercise indirectly optimises sleep quality through a dynamic and synergistic mechanism involving the enhancement of self-efficacy and emotional control. This study provides theoretical support and practical pathways for sleep quality interventions in college students.